2017
DOI: 10.1111/aor.12974
|View full text |Cite
|
Sign up to set email alerts
|

Stable Control of Physiological Parameters, But Not Infection, in Preterm Lambs Maintained on Ex Vivo Uterine Environment Therapy

Abstract: Ex vivo uterine environment (EVE) therapy is an experimental neonatal intensive care strategy wherein gas exchange is performed by membranous oxygenators attached to the umbilical vessels. Our aim was to assess the ability of a newly refined EVE system to maintain key physiological parameters in preterm lambs within optimal ranges for 48 h. EVE group; n = 6: Preterm lambs were delivered under general anesthesia at 115 ± 2 days of gestational age. Animals were submerged in a bath of artificial amniotic fluid on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
(46 reference statements)
1
30
0
Order By: Relevance
“…In previous reports based on our EVE system we demonstrated healthy fetal survival for a period of hours (h), and further extended that to 336 h in a subsequent set of unpublished experiments. [7][8][9][10] Other investigators have reported the successful application of artificial-placenta based therapies for up to h with similar concepts and extracorporeal gas exchange systems. [11][12][13][14] Accordingly, the feasibility of long survival with a pumpless extracorporeal system has been well documented in the experimental literature.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In previous reports based on our EVE system we demonstrated healthy fetal survival for a period of hours (h), and further extended that to 336 h in a subsequent set of unpublished experiments. [7][8][9][10] Other investigators have reported the successful application of artificial-placenta based therapies for up to h with similar concepts and extracorporeal gas exchange systems. [11][12][13][14] Accordingly, the feasibility of long survival with a pumpless extracorporeal system has been well documented in the experimental literature.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In 2019, several groups have shown that important components of fetal physiology are maintained on artificial placental support and develop more naturally than in a ventilated newborn. Stable cardiovascular physiology has been shown both in short‐ and in long‐term experiments using a pumpless system . Even after longer term support, animals can be transitioned to normal care and maintain normal behaviour and mitochondrial respiration .…”
Section: The Artificial Placentamentioning
confidence: 99%
“…Stable cardiovascular physiology has been shown both in short-and in long-term experiments using a pumpless system. 54,55 Even after longer term support, animals can be transitioned to normal care 53 and maintain normal behaviour and mitochondrial respiration. 56 Previous experiments with a pump-driven system had already shown that fetal splenic development 57 and cerebral oxygenation can be maintained 58 and that white matter integrity is preserved with this type of life support.…”
Section: The Artificial Placentamentioning
confidence: 99%
“…Thus, the artificial placenta may be characterized as an ex vivo uterine environment (EVE) wherein gas exchange is performed by membrane oxygenators attached to the umbilical vessels 88‐90 . Experimental use of a newly refined EVE system in five out of six preterm lambs showed maintenance of stable key physiological parameters within optimal ranges for 48 hours 90 .…”
Section: Neonatal Support and Artificial Placentamentioning
confidence: 99%